Stride length determination during overground running using a single foot-mounted inertial measurement unit - Brahms, C. M.; Zhao, Y.; Gerhard, D.; Barden, J. M. (Journal of Biomechanics, 2018)
Changes in postural sway measured via force plate center of pressure have been associated with many aspects of human motor ability. A previous study validated the accuracy and precision of a relatively new, low-cost and portable force plate called the Balance Tracking System (BTrackS). This work compared a laboratory-grade force plate versus BTrackS during human-like dynamic sway conditions generated by an inverted pendulum device. The present study sought to extend previous validation attempts for BTrackS using a more traditional point of application (POA) approach. Computer numerical control (CNC) guided application of ~155 N of force was applied five times to each of 21 points on five different BTrackS Balance Plate (BBP) devices with a hex-nose plunger. Results showed excellent agreement (ICC > 0.999) between the POAs and measured COP by the BBP devices, as well as high accuracy (<1% average percent error) and precision (<0.1 cm average standard deviation of residuals). The ICC between BBP devices was exceptionally high (ICC > 0.999) providing evidence of almost perfect inter-device reliability. Taken together, these results provide an important, static corollary to the previously obtained dynamic COP results from inverted pendulum testing of the BBP.